Towards developing a framework on acceptance of sustainable agriculture among contract farming entrepreneurs - Alby, Jeffrey Lawrence D'Silva; Abu Samah, Bahaman; Uli, Jegak; Mohamed Shaffril, Hayrol Azril (Academic Journals, 2011)
Acceptance of sustainable agriculture practices will undeniably facilitate agricultural entrepreneurs to enhance on their economic and social status, and thus, enable them to enjoy a better livelihood. The focus of this paper is to determine the likely factors that will influence the level of acceptance of sustainable agriculture among contract farming entrepreneurs. Data were collected based on literature analyses. Various factors were identified and it will be a useful input for future researchers that are seeking directions to investigate on the determinants of contract farming entrepreneurs’ acceptance of sustainable agriculture.